The penetration and wettability of varnish in Cryptomeria japonica - Fonte, Ana Paula Namikata da; Carneiro, Mayara Elita; Muniz, Graciela I de Bolzon (Floresta, 2018)
Wood products require preservative and finishing treatments to raise their quality and market value, thus making their appearance more pleasing and their strength higher. The objective of this work was to analyze the wettability of the different finishes, as well as the penetration of the products by scanning electron microscopy. The present study used Scanning Electron Microscopy (SEM) with two replicates per sample and a Goniometer to observe the behaviour of the sessile gout with 5 replicates per sample and radial position. It was concluded that the water based varnish presented a diffuse layer when observed in the SEM and the polyurethane varnish formed a film on the substrate thicker than the other treatments. The copal varnish presented a higher contact angle and the nitrocellulose lacquer formed the smallest contact angle. Copal varnish and PU showed higher hydrophobicity and higher resistance to moisture.